The modified trapezoid approach is based on both harmonic and arithmetic means - Mayser Elan Abbas AL-Owaidi (Genius Journals, 2023)
This paper's goal is to present a revised guideline for data point numerical integration. This approach is based on computations of the harmonic and arithmetic means of the points that make up our interval to evaluate the precision of our approach. Numerous comparisons are computed. This procedure produces highly accurate results.
Keywords: Harmonic mean; Heron Ian mean; trapezoidal rule